Short-term seismic precursor anomalies in hydrogen concentration at fault gas stations along the Northern Margin Fault of the Yanqing Basin of Beijing, China - Yang, Mingbo; Liu, Guiping; Chen, Yuxuan; Hua, Peixue; Hu, Leyin; Wang, Zhiguo; Wang, Shanshan; Sun, Xiaoru; Zhou, Yonggang; Zhang, Haichun; Feng, Gang; Gao, Xiang; et al. (Frontiers in Earth Science, 2025)
The Northern Margin Fault of the Yanqing Basin (NMYB Fault) is an important active fault at the intersection of the Zhangjiakou–Bohai (Zhang-Bo) Belt and the Shanxi Belt in North China. The Yanqing Basin, controlled by the NMYB Fault, is rich in escaping gas from hot springs, and previous investigations have indicated that the Yanqing Basin is located in the peak area of upwelling deep fluids from the mantle source material within the Zhang-Bo Belt. Hence, the site is suitable for geochemical gas precursor observations; to facilitate this, five new fault soil gas continuous stations were built on different segments of the NMYB Fault to carry out observations of fault gas (H2 and CO2) concentrations. The five new stations were approximately 50–60 m deep in the bedrock to monitor the release of gas from the depths of the fault. This was the first time that such geochemical station arrays were deployed in the same fault zone at a high density and depth. The results of the deep-hole observations of fault gas within the Yanqing Fault zone show that the time series of the hydrogen (H2) escape gas concentration has a close relationship with recent seismic activities, reflecting different physical processes of YFBF fault activity. The H2 concentration at the observatory was more sensitive to the stress-loading response of the NMYB Fault system.